Zaynab Fawwāz's Feminist Locutions. - Booth, Marilyn (Journal of Arabic Literature, 2021)
Lebanese-Egyptian Zaynab Fawwāz (ca. 1850-1914) was an unusual presence in 1890s Egypt: an immigrant from Shīʿī south Lebanon, without major family support, she created an intellectual place for herself in the Cairo press, generating a forthright voice on women's needs as distinct from "the nation's." Like most Arabophone writers on "the Woman Question," Fawwāz addressed girls' education, but she focused less on domestic training than on work and income, gender-defined dependency, and exploitation. She highlighted gender-prejudiced uses of religious knowledge to further masculine privilege. Framing her arguments within terms of engagement defined by Islamic sharī ʿ ah , she appropriated and redefined keywords for an indigenous feminism. She repurposed the Islamic-Arabic genre of biographical writing for feminist-inflected history writing. I consider how Fawwāz deployed terminology and genre to contest patriarchal readings of Islamic practice sustained by assumptions of masculinist authority. Fawwāz's writings remind us that secularism was never inherent in Arabophone feminist theorizing, nor were the earliest Arab feminisms Western derivatives. Historical assemblages shaped by Islamic (and Christian) worldviews yielded creative syntheses that were firmly indigenous.